Creative thinking and its impact on reengineering hotel service )Comparative field study in premium class hotels( - نعمة مراتب حسين; عباس محمد فاضل (Journal of Economics and Administrative Sciences, 2020)
The research seeks to identify the dimensions of creative thinking and its impact on the re-engineering of hotel service operations by analyzing the correlation and impact between research variables as well as comparing the research sample The importance of the research comes from the need to motivate managers the importance of creative thinking among workers in the researched hotels because it is an essential part in the re-engineering of hotel services. To achieve this a questionnaire was designed containing (33) items that include the independent research variables (creative thinking) and the accredited (re-engineering the hotel service) and distributed to a sample of (50) individuals represented by (Commissioner Director, Deputy Commissioner, Department Director, Division Director) of the workers Excellent class hotels in Baghdad and after analyzing the answers of the sample Several conclusions have been reached, the most important of which indicates the importance of creative thinking in re-engineering the hotel service to keep the hotel organization in keeping with its external environment, and in light of this research, the managers working in hotel organizations recommend a comprehensive periodic review of the hotel’s location in the local and global labor market by evaluating its activities and comparing it with the market requirements the work.